Optimising diagnostic accuracy with the exercise ECG: opportunities for women and men with stable ischaemic heart disease. Issue 2 (1st June 2016) - Shaw, Leslee J; Xie, Joe X; Phillips, Lawrence M; Goyal, Abhinav; Reynolds, Harmony R; Berman, Daniel S; Picard, Michael H; Bhargava, Balram; Devlin, Gerard; Chaitman, Bernard R
Abstract : The exercise ECG is an integral part within the evaluation algorithm for diagnosis and risk stratification of patients with stable ischaemic heart disease (SIHD). There is evidence, both older and new, that the exercise ECG can be an effective and cost-efficient option for patients capable of performing at maximal levels of exercise with suitable resting ECG findings. In this review, we will highlight the major dilemmas in interpreting suspected coronary artery disease symptoms in women and identify optimal strategies for employing exercise ECG as a first-line diagnostic test in the SIHD evaluation algorithm. We will highlight current evidence as well as recent guideline statements on this subject. Trial registration number: NCT01471522; Pre-results.